2020
DOI: 10.3390/pr8111416
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion Gel Formulation Optimization for Burn Wounds: Analysis of Rheological and Sensory Properties

Abstract: Background: Despite the variety of treatment methods for wounds and scars after burns, there are still few effective preparations that can be used in a non-invasive therapy. Recent years have seen significant development of nanomedicine and nanotechnology in the treatment of infection in burn wounds. Proposal: The aim of this work was to develop a formula of a nanoemulsion gel for skin regeneration after burns, and to compare its rheological and sensory properties, as well as the effectiveness of post-burn ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
1
28
0
2
Order By: Relevance
“…The consistency is also a feature that makes the products attractive to consumers. It is worth adding that it affects the effectiveness of the action of creams applied to the skin [ 46 , 49 ]. Due to their intended purpose, protective preparations used in wet environments contain hydrophobic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The consistency is also a feature that makes the products attractive to consumers. It is worth adding that it affects the effectiveness of the action of creams applied to the skin [ 46 , 49 ]. Due to their intended purpose, protective preparations used in wet environments contain hydrophobic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the present study, Kaur and Kapoor 41 in their study stated that in addition to having antibacterial and antifungal properties, the compounds produced from sea buckthorn oil facilitate the wound healing process. The results of the research of Miastkowska et al 42 also showed that the gel made from sea buckthorn by forming a coating layer on the wound, keeping it moist, and also preventing the penetration of external factors into it, facilitates the wound healing process. Goudarzi et al 43 in their study reported that in addition to its anti‐inflammatory properties, sea buckthorn facilitates the wound healing process due to its analgesic and anti‐hypersensitivity effects, moreover.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The o/w or w/o NE can be prepared as liquid (typically less than 20–30% fatty substances) or semi-solid such as creams that maintain the portion of the internal phase between 30–70%. 53 NE can also be prepared as a 3-dimensional network gel using a mucoadhesive polymer such as chitosan. 34 Antimicrobial creams and gel semi-solids can be applied topically to provide an effective means of delivery of the active ingredient directly on the surface of infected areas such as skin or certain mucous membranes.…”
Section: Advances In Ne Delivery Of Antimicrobialsmentioning
confidence: 99%